Transient MHD Convective Flow of Fractional Nanofluid between Vertical Plates - Najma Ahmed; Nehad Ali Shah; Bakhtiar Ahmad; Syed Inayat Shah; Sam Ulhaq; Mohamad Rahimi -Gorji (Journal of Applied and Computational Mechanics, 2019)
Effects of the uniform transverse magnetic field on the transient free convective flows of a nanofluid with generalized thermal transport between two vertical parallel plates have been analyzed. The fluid temperature is described by a time-fractional differential equation with Caputo derivatives. Closed form of the temperature field is obtained by using the Laplace transform and fractional derivatives of the Wright’s functions. A semi-analytical solution for the velocity field is obtained by using the Laplace transform coupled with the numerical algorithms for the inverse Laplace transform elaborated by Stehfest and Tzou. Effects of the derivative fractional order and physical parameters on the nanofluid flow and heat transfer are graphically investigated.